Efforts to Improve Performance - Herbet Sianturi, Rudi; B, Mesra (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
A variety of resources, including people, money, machines, equipment, and information resources, are required to achieve organizational goals. Human resource management is very important for an organization. So in managing it, managing and using human resources will run according to what is expected, so that it can function productively to achieve organizational goals. This research was conducted to examine the influence of competency, integrity and organizational culture on employee performance in moderating job satisfaction at the Bank Indonesia Representative Office, North Sumatra Province. The results of this research are as follows: Organizational culture has a positive and significant effect on employee performance with a value of 0.366 and a significant value of 0.000. Job Satisfaction is not able to moderate Competency on Employee Performance with a value of 0.038, significant 0.129. Job Satisfaction is able to moderate Integrity on Employee Performance with a value of -0.127, significant 0.013. Job Satisfaction is able to moderate Organizational Culture on Employee Performance with a value of 0.120 and a significant value of 0.023. Integrity has a positive and significant effect on employee performance with a value of 0.397 and a significant 0.000. Job satisfaction has a positive and significant effect on employee performance with a value of 0.278, significant 0.000. Competency has a positive and insignificant effect on employee performance with a value of 0.007, significant 0.377.